The Influence of Product Quality, Service Quality, Customer Satisfaction on Customer Loyalty at Pizza Hut Restaurant - Hanindita, Lisa Putri; Riorini, Sri Vandayuli (prodima@fe.uika-bogor.ac.id, 2023)
This research aims at product quality, service quality, customer satisfaction, and customer loyalty. The sampling technique used was purposive sample, that is people who have eaten at a pizza hut restaurant with a total of 125 respondents used by deploying google form. Hypothesis testing using a partial test (t test), simultaneous test (F test), and the coefficient of determination (R²). The test results prove that product quality, service quality, and customer satisfaction have a positive effect on customer loyalty.